2010
DOI: 10.3395/reciis.v4i1.349en
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the health care workplace: a theme for international cooperation in human resources in the health sector

Abstract: Entre os temas dos recursos humanos em saúde vêm recebendo maior atenção as condições de trabalho e os riscos para a saúde dos trabalhadores, dentre os quais, de acordo com o Relatório Mundial da Saúde de 2006, consta a violência no trabalho. A partir do estudo da literatura e de documentos oficiais, o presente artigo procura evidenciar a relevância do problema e identificar elementos para elaboração de estratégias de cooperação internacional nesse tema. Estudos mostram que as agressões podem ultrapassar larga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Patients, who are increasingly more aware of their rights and have high expectations, often face a malfunctioning healthcare system with its understaffing, poor funding and high workload of the personnel. This, in turn, can generate dissatisfaction, frustration and a feeling of injustice, all leading to an escalation in aggression [1,2]. Analyses have shown that the healthcare and social work sectors have a very high prevalence of workplace violence [3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients, who are increasingly more aware of their rights and have high expectations, often face a malfunctioning healthcare system with its understaffing, poor funding and high workload of the personnel. This, in turn, can generate dissatisfaction, frustration and a feeling of injustice, all leading to an escalation in aggression [1,2]. Analyses have shown that the healthcare and social work sectors have a very high prevalence of workplace violence [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the occupational sphere, health workers are the most affected victims, with a fourth of all cases of violence at work (3) . This group has direct contact with the public in its professional activities (3) and often works in places that enhance violence (4) .…”
Section: Introductionmentioning
confidence: 99%
“…In the occupational sphere, health workers are the most affected victims, with a fourth of all cases of violence at work (3) . This group has direct contact with the public in its professional activities (3) and often works in places that enhance violence (4) . In the context of health workers' reality, the professional group violence most strongly affects is nursing (3,5,6) , explained by its very close contact with patients during nursing care delivery (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of nurses have experienced physical violence, which may, among others, take the form of beating, kicking, slapping, stabbing, shooting, pushing, biting, and/or pinching, or nonphysical violence such as verbal abuse, bullying/mobbing, harassment, and threats, or a combination of both types of violence (Camerino, Estryn-Behar, Conway, van Der Heijden, & Hasselhorn, 2008;Spector, Zhou, & Che, 2014). Nurses play a central role within health care teams: working antisocial shift patterns and their frequent contact with the public being factors linked to the highest risk of violence (Campos & Pierantoni, 2010;Kowalczuk & Krajewska-Kułak, 2017;Papa & Venella, 2013). According to the literature, the most common sources of violence against nurses are not only patients and their relatives but also other medical staff.…”
Section: Introductionmentioning
confidence: 99%